Metal Complexes of 5, 15‐Porphyrinquinones: Systematic Study of Crystal Structure, Electronic Structure, and Lewis Acidity. Issue 36 (2nd July 2020) - Yamashita, Ken‐ichi; Hirano, Daisuke; Sugiura, Ken‐ichi
Abstract : We conducted the first systematic study on the synthesis, structure, and properties of various divalent metal complexes (Ni II, Cu II, Zn II, Pd II, Pt II, and Pb II ) of 5, 15‐porphyrinquinone (PQ, a quinone compound of porphyrin) for diversifying the chemistry of traditional quinone‐metal complexes. Similar to electron‐accepting nature of PQ, the metal complexes studied here also exhibit it. Ni II, Pd II, and Pt II complexes favor face‐to‐face stacked structures in the crystals, thus inducing effective Pt II –Pt II interaction, which has not been observed in the porphyrin analogues to date. Ultraviolet‐visible (UV/Vis) absorption spectra of the metal complexes vary widely depending on the metal ion and owing to the effective d(metal)–π(PQ) coupling in their molecular orbitals. Quantitative analyses of the axial ligation on the central metal ions (Ni II and Cu II ) revealed significantly larger binding constants than those of the porphyrin analogues, indicating significant enhancement of their Lewis acidities due to the strong electron‐withdrawing nature of PQ. Abstract : Aimed at the expansion of the chemistry of quinone‐metal complexes, the systematic study of divalent metal complexes of 5, 15‐porphyrinquinone revealed their strong electron‐accepting nature and metal–metal interaction (for Pt), effective d(metal)–π(ligand) coupling in their molecular orbital, and their great enhancement of the Lewis acidity of the central metals.